PENERAPAN SISTEM E-LEARNING PADA SEKOLAH MTS DARUL MUTTAQIN AL-AMIN KOTA DEPOK: E-Learning;User Satisfaction;Website Quality. - Suryani, Nining; Hakim, Lukman; Cahya Putri Buani, Duwi (JURNAL AKADEMIKA, 2020)
Advances in the form of technology education system has replaced the role of the application of manual learning known to society in general to be developed in the form of electronic learning (e-learning) in an effort to improve learning effective and efficient, so that learning activities become flexible. In this analysis the method used is waterfall, this waterfall model for details of the project activities into a linear sequential phase, where each phase depends on the previous post PDA and according to the task Sepesialization. Based on the analysis of the effectiveness of learning teaching in the school MTS Darul Muttaqin AL-Amin, Depok, conclude that the application of learning to teach electronically (E-learning) A learning media option and seeks to facilitate teachers and students in the learning process in order to provide a more effective and efficient learning system, improve self-learning ability, provide the flexibility of learning interactions both in terms of time and place, make students more sensitive to the advancement of technology, and make the learning atmosphere more enjoyable.